1997
DOI: 10.1021/ma970680z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Inclusion Complexes of Aliphatic Polyesters with Cyclodextrins

Abstract: Cyclodextrins (CDs) were found to form inclusion complexes with aliphatic polyesters [-O(CH2)xOCO(CH2)4CO]n (where x ) 2, 3, or 4) to give crystalline compounds. R-and γ-CD formed complexes with these polyesters in high yields, although β-CD gave complexes in moderate yields. Although the yields of the complexes of R-CD with poly(trimethylene adipate) (PTA) (x ) 3) and poly-(1,4-butylene adipate) (PBA) (x ) 4) decreased with increasing molecular weight, R-CD formed complexes with poly(ethylene adipate) (PEA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
135
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(145 citation statements)
references
References 16 publications
8
135
0
2
Order By: Relevance
“…[1,2] Cyclodextrins (CDs) form inclusion complexes with some organic polymers, [3][4][5][6] such as poly(ethylene glycol), poly(propylene glycol), [7,8] polyesters, [9][10][11] poly(propylene)s, [12] poly(methyl vinyl ether), [13] polyamine, [14] poly(dimethylsiloxane)s, [15] poly(dimethylsilane)s, [16] polyisoprene, [17] and poly(methyl acrylate), [18] to…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Cyclodextrins (CDs) form inclusion complexes with some organic polymers, [3][4][5][6] such as poly(ethylene glycol), poly(propylene glycol), [7,8] polyesters, [9][10][11] poly(propylene)s, [12] poly(methyl vinyl ether), [13] polyamine, [14] poly(dimethylsiloxane)s, [15] poly(dimethylsilane)s, [16] polyisoprene, [17] and poly(methyl acrylate), [18] to…”
Section: Introductionmentioning
confidence: 99%
“…Ritter et al studied sidechain polyrotaxanes utilizing CyDs and a polymethacrylate or poly(ether sulfone) as a main chain [18][19][20] . Harada et al investigated macromolecular recognition by CyDs with poly(ethylene glycol) (PEG), poly(propylene glycol) (PPG), poly(isobutylene), and polyesters as a family of polyrotaxanes [21][22][23][24][25][26][27] . We have studied biodegradable polyrotaxanes consisting of a-CyDs and PEG for pharmaceutical and biomedical applications [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Because the driving force for such an inclusion complexation of CyDs with a polymeric chain is due to intermolecular hydrogen bondings between neighboring CyDs as well as steric fittings and the hydrophobic interaction between host and guest molecules [21][22][23][24][25][26][27]34) , several stimuli such as temperature and dielectric change may be used to control the assembled state of CyDs in a polyrotaxane. We have found that a polyrotaxane consisting of many bCyDs and a triblock copolymer of PEG and PPG capped with naphthylamine exhibits the dynamic characteristics of a molecular piston: the soluble-insoluble nature of the polyrotaxane is controlled by temperature, presumably due to switching the assembled and dispersed states of bCyDs along the triblock copolymer 32,33) .…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] It is known that partially and fully methylated CDs can also form ICs and the stability of the ICs formed depends on the size and shape of the guest molecule. [10] While there have been so many publications about the inclusion phenomena of the natural CDs with polymers, such as poly(e-caprolactone), poly(ethylene adipate), poly(trimethylene adipate), and poly(1,4-butylene adipate), [11][12][13][14][15] only a few investigations on the complex formation of modified CD with polymers have been reported. [9,[16][17][18][19][20][21] Okada et al [9] found that methylated CDs selectively form ICs with hydrophobic polymers and that the hydrophobic interaction between methylated CDs and polymers is one of the most important factors for complexation, as found also for unmodified CDs.…”
Section: Introductionmentioning
confidence: 99%